Facial Recognition and Posthuman Technologies in Shakespeare’s Sonnets - Robert Darcy (Multicultural Shakespeare, 2021)
The human face, real and imagined, has long figured into various forms of cultural and personal recognition—to include citizenship, in both the modern and the ancient world. But beyond affiliations related to borders and government, the human face has also figured prominently into biometrics that feed posthuman questions and anxieties. For while one requirement of biometrics is concerned with “unicity,” or that which identifies an individual as unique, another requirement is that it identify “universality,” confirming an individual’s membership in the species. Shakespeare’s sonnets grapple with the crisis of encountering a universal beauty in a unique specimen to which Time and Nature nonetheless afford no special privilege. Between fair and dark lies a posthuman lament over the injustice of natural law and the social valorizations arbitrarily marshaled to defend it.